India–China Intra-Industry Trade: Analysis of India’s Route Toward Global Production Sharing - Das, Riya; Sarma, Amiya (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : The goal of this study was to evaluate the degree of intra-industry trade (IIT) that exists between China and India while taking vertical specialization into account. We looked into the amount of IIT between these two Asian trading giants because of Asia’s increasing involvement in global production sharing and the contribution of vertical specialization to intra-industry trade within Asia. Methodology : The study was based on 20 years’ worth of secondary bilateral commodity trade data at the HS two-digit level (2002–2021). The adjusted Grubel–Lloyd index was used to compute the IIT between China and India. The unit value dispersion technique was then used to further divide the overall IIT into vertical and horizontal sub-industry trade. Findings : It has been observed that there has been a noteworthy increase in India’s IIT with China over the years, with a distinct trend of commodities displaying vertical differentiation. This result indicated that the structure of bilateral commerce between China and India was significantly influenced by cross-border manufacturing fragmentation. Practical Implications : The study’s findings underscored the urgent requirement for targeted policy interventions across industries to tackle India’s trade dynamics with China. Sector-specific methods were considered necessary in order to recognize the predominance of commodities with the vertical difference in bilateral commerce. Originality : The current study specifically focused on analyzing the bilateral IIT between two significant emerging countries in Asia, in contrast to previous research on the vertical specialization aspect of IIT in Asia, which primarily examined IIT on a multilateral basis.